2009
DOI: 10.1080/09513590903015510
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal replacement therapy in women with Turner's syndrome in Poland: Analysis of 176 cases

Abstract: (1) Large percentage of women with TS does not use HRT. (2) Women with TS, who receive HRT, use this method of treatment insufficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Finally, it seems important to comment on the significantly higher FSH levels and the percentage of patients with FSH > 40 IU/L in GH+ group as compared to GH−, which was difficult to account for. In our previous study, we reported that a large percentage of women with TS did not use HRT; those who did used this method of treatment insufficiently, i.e., HRT doses were most likely too low 36 . However, some local effects of GH or GH degradation products on the secretion of other anterior pituitary hormones cannot be ruled out.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, it seems important to comment on the significantly higher FSH levels and the percentage of patients with FSH > 40 IU/L in GH+ group as compared to GH−, which was difficult to account for. In our previous study, we reported that a large percentage of women with TS did not use HRT; those who did used this method of treatment insufficiently, i.e., HRT doses were most likely too low 36 . However, some local effects of GH or GH degradation products on the secretion of other anterior pituitary hormones cannot be ruled out.…”
Section: Discussionmentioning
confidence: 94%
“…Although about 40% of these young women reported health problems, almost 13% did not consult any physician. According to one study, 14% did not take oestrogen replacement therapy (120), whilst in another, only half of young adults with TS used HRT (121).…”
Section: Complex Health Care During Transition In Studiesmentioning
confidence: 99%
“…In order to maintain feminisation and prevent osteoporosis, oestrogen replacement is usually required until the time of normal menopause (Table 4) (2). Still, recent studies have shown that a considerable percentage of TS patients discontinue therapy in adult life (120,121).…”
Section: Puberty/fertility In Transition Timementioning
confidence: 99%